Cost to government and society of chronic kidney disease stage 1–5: a national cohort study. Issue 7 (July 2015) - Wyld, M. L. R.; Lee, C. M. Y.; Zhuo, X.; White, S.; Shaw, J. E.; Morton, R. L.; Colagiuri, S.; Chadban, S. J.
Abstract Background Costs associated with chronic kidney disease (CKD) are not well documented. Understanding such costs is important to inform economic evaluations of prevention strategies and treatment options. Aim To estimate the costs associated with CKD in Australia. Methods We used data from the 2004/2005 AusDiab study, a national longitudinal population‐based study of non‐institutionalised Australian adults aged ≥25 years. We included 6138 participants with CKD, diabetes and healthcare cost data. The annual age and sex‐adjusted costs per person were estimated using a generalised linear model. Costs were inflated from 2005 to 2012 Australian dollars using best practice methods. Results Among 6138 study participants, there was a significant difference in the per‐person annual direct healthcare costs by CKD status, increasing from $1829 (95% confidence interval (CI): $1740–1943) for those without CKD to $14 545 (95% CI: $5680–44 842) for those with stage 4 or 5 CKD (P < 0.01). Similarly, there was a significant difference in the per‐person annual direct non‐healthcare costs by CKD status from $524 (95% CI: $413–641) for those without CKD to $2349 (95% CI: $386–5156) for those with stage 4 or 5 CKD (P < 0.01). Diabetes is a common cause of CKD and is associated with increased health costs. Costs per person were higher for those with diabetes than those without diabetes in all CKD groups; however, this was significant only for those without CKD and those with early stage (stage 1 or 2) CKD. Conclusion Individuals with CKD incur 85% higher healthcare costs and 50% higher government subsidies than individuals without CKD, and costs increase by CKD stage. Primary and secondary prevention strategies may reduce costs and warrant further consideration.